INFLUENCE OF DESIGN ELEMENTS OF THE CASTING ON THE EVOLUTION OF TECHNOLOGICAL DEFECTS (Modern Problems of Metallurgy, 2021)
The formation of product quality parameters, their performance characteristics and reliability indicators are closely related with the important substages and stages of the Products Life Cycles. The differences between the predicted and real values of the functional parameters of products during their Life Cycles indicate the disadvantages in the solving of the tasks using only the theoretical methods. The initial structure and initial properties of the blanks should be considered in close relations with the heredity of the material, starting from the melt smelting. About 25% of the quality parameters of the original material are transferred from the blank, and about 75% are formed during casting and crystallization of the liquid melt during cooling. The local nature of fracture during cutting determines to needs to analyze the process of accumulation of technological defects in materials (alloys) and predict their degeneration into the technological damages under adverse operating conditions of products. The method of LM-hardness, developed under the guidance of Academician A.O Lebedev, are used effectively to solve applied engineering problems. A characteristic feature of the LM – hardness method is to use of the degree of scattering of the characteristics of the mechanical properties of the material samples after operation at different stress levels, such as hardness, for the analysis of material damages degree. The actual damages degree of the product material and the intensity of its increasing are used to analyze the processes of material degradation during the operation stage of the machine parts. In this paper a criterion of technological damageability of the product material for the analysis of structural changes during castings manufacturing is proposed. Experimental researches for casting in sand molds from aluminum alloy AK21M2.5H2.5 GOST 1853-93 are realized. Based on the results of experimental studies, the distribution of technological defects in the material is determined and the minimum values of allowances for processing of aluminum alloy castings with stress concentrators are established.
Keywords: blank; blank castingblank casting; casting; Product Life Cycle; technological process; technological inheritability; homogeneity; technological damageability